2021
DOI: 10.1210/clinem/dgab707
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Wnt/β-Catenin and ACTH Signaling Pathways and Paracrine Regulation in Aldosterone-producing Adenoma

Abstract: Context Aldosterone-producing adenomas (APA) are a common cause of primary aldosteronism. Despite the discovery of somatic mutations in APA and characterization of multiple factors regulating adrenal differentiation and function, the sequence of events leading to APA formation remains to be determined. Objective We investigated the role of Wnt/β-catenin and ACTH signaling, as well as elements of paracrine regulation of aldost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Another study found transitional structures with a combination of subcapsular APM-like structure and an inner APA-like microstructure without well-defined borders, characterized by the presence of KCNJ5 and ATP1A1 mutations [ 35 ]. Recently, two further studies documented that APMs in the adrenals of patients with APAs carried mutations predominantly in CACNA1D , but also in KCNJ5, ATP1A1 , CACNA1H , PRKACA and CTNNB1, weakening the hypothesis that KCNJ5 mutations do not correlate with the APM-APA transition theory [ 36 , 37 ]. The presence of somatic mutations in APMs suggests that co-driver mutations are necessary in order to promote APA formation.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found transitional structures with a combination of subcapsular APM-like structure and an inner APA-like microstructure without well-defined borders, characterized by the presence of KCNJ5 and ATP1A1 mutations [ 35 ]. Recently, two further studies documented that APMs in the adrenals of patients with APAs carried mutations predominantly in CACNA1D , but also in KCNJ5, ATP1A1 , CACNA1H , PRKACA and CTNNB1, weakening the hypothesis that KCNJ5 mutations do not correlate with the APM-APA transition theory [ 36 , 37 ]. The presence of somatic mutations in APMs suggests that co-driver mutations are necessary in order to promote APA formation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have investigated the relationship between different signaling pathways and components of the microenvironment in adrenals with APA. We have applied multiplex immunofluorescence and multispectral image analysis to investigate the colocalization of proteins involved in aldosterone (CYP11B2) and cortisol (CYP11B1/CYP17A1) biosynthesis, markers of Wnt/β-catenin (β-catenin) and ACTH/cAMP/PKA (MC2R, pCREB) signaling, as well as paracrine pathways of the tumor microenvironment (Tryptase, S100) and vascularization (CD34) ( 100 ). Our results show a dense vascularization in APA, which is independent of the somatic mutation status of the tumor.…”
Section: Interplay Between Vascular and Hormonal Components In Primar...mentioning
confidence: 99%
“…The synthesis of aldosterone in APM was further determined by mass spectrometry-based imaging studies [66,67]. Both APA and APM have elevated Wnt/β-catenin activity and alterations in CYP11B2 methylation, which may influence their production of aldosterone [68 ▪▪ ,69 ▪ ]. A recent study demonstrated the presence of significant amount of mast cells in APMs as well as in APAs [68 ▪▪ ].…”
Section: Cellular Origins Of Adrenal Aldosterone Productionmentioning
confidence: 99%
“…Both APA and APM have elevated Wnt/β-catenin activity and alterations in CYP11B2 methylation, which may influence their production of aldosterone [68 ▪▪ ,69 ▪ ]. A recent study demonstrated the presence of significant amount of mast cells in APMs as well as in APAs [68 ▪▪ ]. Degranulation of mast cells can stimulate aldosterone production through the local release of serotonin and activation of the 5-HT4 receptor [70,71].…”
Section: Cellular Origins Of Adrenal Aldosterone Productionmentioning
confidence: 99%
See 1 more Smart Citation